Tafarrud in Hadith Studies: The Status of Narrations Transmitted by a Single Companion - Faisal Amri Al-Azhari (Yayasan Bayt Shufiya Nusantara, 2026)
This study analyzes the status of a single of the Shahabah (tafarrud ash-shahabi) in Hadith studies, focusing on the principle of “laa yadhurru shihhata al-hadith tafarrud shahabi bihi”. Although hadith classification quantitatively divides narrations into mutawatir (mass-transmitted) and ahad (solitary), a qualitative debate persists regarding the evidentiary value (hujjah) of a single transmission, particularly concerning creed (aqidah) and legal rulings (ahkam). This qualitative research utilizes a literature review method (historical-analytical approach) to evaluate classical and contemporary hadith literature, specifically focusing on the critique by Ibn al-Qayyim in Ighathat al-Lahfan. The results demonstrate that the majority of Ahlus Sunnah wal Jama'ah scholars uphold the concept of collective integrity (‘adalah) of all Shahabah, thereby establishing that a solitary narration by a Companion is not categorized as an anomaly (shadh) but remains a valid proof (hujjah), provided that the chain of transmission (sanad) is contiguous and authentic. These findings reveal that historical rejections raised against tafarrud by groups such as the Mu'tazilah, Rafidhah, and certain Zahiriyah have been systematically refuted by early jurists, affirming that the quantitative number of narrators is not a prerequisite for authenticity at the level of the Shahabah.